1998
DOI: 10.1007/s004410051142
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical observation of growth-associated protein 43 (GAP-43) in the developing circumvallate papilla of the rat

Abstract: The distribution and development of growth-associated protein 43 (GAP-43)-like immunoreactivity (-LI) in the rat circumvallate papilla (CVP) were compared to those of protein gene product 9.5 (PGP 9.5)-LI. In the adult, thick GAP-43-like immunoreactive (-IR) structures gathered densely in the subgemmal region. Some of these further penetrated the apical epithelium and trench wall epithelium. At least two types of GAP-43-IR structures were recognized; taste bud-related and non-gustatory GAP-43-IR neural element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Similar pattern was demonstrated in the vallate papilla (AhPin et al, 1989;Hirata and Kanaseki, 1989;Wakisaka et al, 1996Wakisaka et al, , 1998Mbiene and Roberts, 2003). However, in contrast to NP, there was drastic shortfall in taste buds in the apical epithelium with few remaining in the adult vallate papilla.…”
supporting
confidence: 74%
“…Similar pattern was demonstrated in the vallate papilla (AhPin et al, 1989;Hirata and Kanaseki, 1989;Wakisaka et al, 1996Wakisaka et al, , 1998Mbiene and Roberts, 2003). However, in contrast to NP, there was drastic shortfall in taste buds in the apical epithelium with few remaining in the adult vallate papilla.…”
supporting
confidence: 74%
“…It is a good marker for fine peripheral nerve fibers and has been extensively used for the study of lingual and gustatory papillae innervation (AhPin et al 1989; Wakisaka et al 1996Wakisaka et al , 1998Mbiene and Mistretta 1997;Ringstedt et al 1999). Wakisaka et al (1996) reported the presence of PGP 9.5-IR nerve fibers and neurons in the vallate papilla in the developing mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Taste buds/taste bud progenitors were visualized by an antibody to cytokeratin 8 (Troma-1; Knapp et al 1995;Zhang et al 1995). The antibody to GAP-43 was used to assess innervation (Mistretta and Haus 1996;Wakisaka et al 1998;Ringstedt et al 1999). Samples fixed in 10% acetic acid in 70% ethanol were incubated with antibodies against Troma-1 (1:80, Hybridoma Bank, Iowa City, Iowa, USA) and GAP-43 (1:200, Chemicon, Temecula, Calif., USA) for 48-72 h at 4°C, rinsed in PBS, and incubated at room temperature for 2 h with Alexa-488-conjugated anti-rabbit IgG (1:400; Molecular Probes, Eugene, Ore., USA) and Alexa-594-conjugated anti-rat IgG (1:400; Molecular Probes).…”
Section: Methodsmentioning
confidence: 99%